Framing Islam Wasathiyah dalam Media Massa: Analisis Isi Berita Keislaman - Sulthan Dafa Al Farizzi (Raudhatun Najah Publisher, 2023)
This study aims to analyze how Wasathiyah Islam is framed in national mass media coverage and how the construction of the meaning of Islamic moderation is formed through Islamic news texts. The main focus of this study is to identify the pattern of representation of Wasathiyah Islam in mainstream media and the framing strategies used in shaping public perception of the concept of moderate Islam in Indonesia. This research uses a qualitative approach with a content analysis method based on Robert N. Entman’s framing model. The research data were obtained through documentation of Islamic news from national media such as Kompas, Republika, CNN Indonesia, and Tempo within a certain period relevant to the research focus. The analysis was conducted by examining framing elements, including problem definition, causal interpretation, moral evaluation, and treatment recommendation in each news item related to Wasathiyah Islam. The results show that Wasathiyah Islam in mass media is generally framed positively as a symbol of moderate Islam associated with tolerance, peace, and nationalism. However, this framing is still influenced by political dynamics, media ideology, and the logic of the media industry. As a result, the representation of Wasathiyah Islam is not always consistent and tends to be situational.